ISSUANCE OF LETTER OF APPROVAL FOR SAILING AT COASTAL FISHING PORT (CFP) MAYANGAN - Adnyana, I Putu Agus; Sari, Iya Purnama (Politeknik Kelautan dan Perikanan Dumai, 2024)
One of the main duties of the harbor master is to issue sailing approvals to ensure order and security of the ship and crew when sailing at sea. The sailing approval letter is a state document issued to every fishing vessel that will sail by the harbormaster. The uncertainty of time, schedule and so on in processing the issuance of the sailing approval letter indicates the importance of having a clear flow and procedure in issuing the sailing approval letter. This research aims to find out the procedures for issuing a sailing approval letter. The research was carried out in May - June 2023. This research was carried out at the Mayangan Coastal Fishing Port (CFP). Data collection was carried out using the observation method and analyzed using a qualitative approach. The procedure for issuing a sailing approval letter at CFP Mayangan is quite good. However, there is still a need for improvement and enhancement in the issuance of sailing approval letter in Mayangan. These include improvements to the application system in order to expedite the application process, socialization to fishermen or sailing approval letter applicant agents regarding online applications, time management by the syahbandar to make the sailing approval letter issuance faster and more effective and efficient.